Breathlessness despite optimal pathophysiological treatment: on the relevance of being chronic. Issue 3 (28th September 2017) - Morélot-Panzini, Capucine; Adler, Dan; Aguilaniu, Bernard; Allard, Etienne; Bautin, Nathalie; Beaumont, Marc; Blanc, François-Xavier; Chenivesse, Cécile; Dangers, Laurence; Delclaux, Christophe; Demoule, Alexandre; Devillier, Philippe; et al.
In the May 2017 issue of the European Respiratory Journal ( ERJ ), Johnson et al . [1] proposed the term "chronic breathlessness syndrome" to describe the clinical situation in which "breathlessness that persists despite optimal treatment of the underlying pathophysiology and results in disability for the patient". The term "disability" in this definition corresponds to "physical limitations and/or a variety of adverse psychosocial, spiritual or other consequences", which very closely matches the World Health Organization definition of the word [2]. The relationship between breathlessness and disability was well captured in the foreword of a document published in 2013 by the Forum of International Respiratory Societies [3], which begins: "When we are healthy, we take our breathing for granted […]. But when our lung health is impaired, nothing else but our breathing really matters". This has become the "catch phrase" of the French lung health foundation ("Fondation du Souffle", www.lesouffle.org ). The explicit definition of "chronic breathlessness" as proposed by Johnson et al . [1] differs very little from the implicit definition of "refractory breathlessness", the term previously used in many studies, and which was proposed as a distinct entity by some of the authors of a previously published ERJ article [4]. Johnson et al . [1] submit that defining and naming this new syndrome will improve the visibility of a distressing and debilitating condition that is too often overlooked and neglected [5]. They postulate that this enhanced visibility will result in improved care and organisation of care, stronger research [6], and greater empowerment for patients and their caregivers. The Editorial by Başoğlu [7] published in the May 2017 issue of the ERJ throws new light on this notion of empowerment. Making a daring but fascinating parallel between untreated dyspnoea and torture, Başoğlu [7] reminds us how and why addressing dyspnoea in general (and probably "chronic breathlessness" in particular) is a fundamental issue not only from the point of view of medicine per se, but also from the point of view of human rights (on this, see also [8]). He also makes a very convincing case for the importance of empowerment in the management of dyspnoea. Still in the same issue of the ERJ, Calverley [9] comments on the new syndrome and, like us, concurs with Johnson et al . [1] about the relevance of making breathlessness a foremost concern of every clinician. Despite maximal pathophysiological treatment, persistent dyspnoea is a distinct entity, be it chronic or acute http://ow.ly/7cR530equaI